A self-assembling graphene oxide coating for enhanced bactericidal and osteogenic properties of poly-ether-ether-ketone - Huang, Run; Gu, Yingjian; Yuan, Yeju; Wang, Yunxiao; Pan, Yusong; Li, Bo; Ren, Geliang; Huang, Lei; Xie, Yinghai (Frontiers in Bioengineering and Biotechnology, 2024)
Poly-ether-ether-ketone (PEEK) is a biomedical plastic that can be used for orthopedic implants, but it offers poor antibacterial properties and bioactivity. In this study, PEEK was sulfonated with the obtained porous structure adsorbing graphene oxide (GO). The surface microstructures and properties of the original PEEK, sulfonated PEEK (SPEEK), and GO-grafted PEEK (GO-SPEEK) were characterized. The results revealed that the GO-SPEEK surface is a 3D porous structure exhibiting superior hydrophilicity to the original PEEK. Although SPEEK was shown to possess antimicrobial properties against both Escherichia coli and Staphylococcus aureus, the bactericidal effect was even more significant for GO-SPEEK, at about 86% and 94%, respectively. In addition, the in vitro simulated-body-fluid immersion and cell experiments indicated that GO-SPEEK had much better hydroxyapatite (HA)-precipitation induction capacity and cell–material interactions (e.g., cell adhesion, proliferation, osteodifferentiation, and extracellular matrix mineralization. The tensile test revealed that the mechanical properties of PEEK were maintained after surface modification, as GO-SPEEK has comparable values of elastic modulus and tensile strength to PEEK. Our investigation sought a method to simultaneously endow PEEK with both good antimicrobial properties and bioactivity as well as mechanical properties, providing a theoretical basis for developing high-performance orthopedic implants in the clinic.